Plasma Adropin Levels Predict Endothelial Dysfunction Like Flow-Mediated Dilatation in Patients With Type 2 Diabetes Mellitus - Topuz, Mustafa; Celik, Ahmet; Aslantas, Tutku; Demir, Ayse Kevser; Aydin, Suna; Aydin, Suleyman (Lippincott Williams & Wilkins, 2013)
Objective: This study investigated the role of plasma adropin levels to show endothelial dysfunction in individuals with type 2 diabetes mellitus and to compare these with flow-mediated dilatation. Methods: A total of 92 individuals with diagnosed type 2 diabetes mellitus were included and divided into 2 groups according to their brachial flow-mediated dilatation. The endothelial dysfunction group consisted of 46 participants with flow-mediated dilatation change of less than 7%, whereas 46 participants with flow-mediated dilatation change of more than 7% were accepted as the nonendothelial dysfunction group. Venous blood samples were taken from all study participants, and plasma adropin levels were measured using an enzyme-linked immunosorbent assay kit. Results: The mean flow-mediated dilatation values were 13.2% +/- 4.9% in the nonendothelial dysfunction group, and 3.5% +/- 3.4% in the endothelial dysfunction group. Mean hemoglobin A(1c) levels were significantly higher in the endothelial dysfunction group than in the nonendothelial dysfunction group (8.7% +/- 1.9% vs 7.9% +/- 1.6%, respectively; P < 0.038). Mean plasma adropin levels were 3.04 T 0.79 ng/mL in the endothelial dysfunction group and 4.67 +/- 1.43 ng/mL in the nonendothelial dysfunction group; P < 0.001. Plasma adropin levels showed no correlation with body mass index (r = -0.072, P = 0.497) but were positively correlated with flow-mediated dilatation values (r = 0.537, P < 0.001). In the linear regression analysis, adropin and hemoglobin A(1c) were independent risk factors for endothelial dysfunction in individuals with type 2 diabetes mellitus. Conclusion: Adropin is a new marker for use in demonstrating endothelial dysfunction.
Keywords: Adropin; flow-mediated dilatation; endothelial dysfunction; type 2 diabetes mellitus; endothelium